Christ’s Agony and Faith’s Wakefulness: Reflections on a Remark of Pascal - Ziegler, Philip G. (Toronto journal of theology, 2022)
This essay reflects upon a remark of Blaise Pascal. His gloss upon the story of Christ in Gethsemane is punctuated with the arresting comment that "Jesus will be in agony even to the end of the world: during that time, we must not sleep" — "Jésus sera en agonie jusqu’à las fin du monde: Il ne faut pas dormir pendant ce temps-là". In close conversation with the work of Lev Shestov, I explore the unsettling suggestion that for Christian faith the time before the eschaton is fundamentally "gethesemanean" in quality, i.e., is marked by Christ’s own saving agon and so also by faith’s proper struggle to awaken to it and keep vigil with it. For Shestov, Pascal’s disquieting vision demands that the Christian life "seeks with lamentation" to resist the false consolation of trading the travail of discipleship for the confidence of clear understanding. To the agony of Christ there corresponds the agon of faith: it is the labour of discipleship to shake off the sleep of reason in the time that remains.